Why Are There So Few Basidiomycota and Basal Fungi as Endophytes? A Review - Nattawut Rungjindamai; E. B. Gareth Jones (My University, 2024)
A review of selected studies on fungal endophytes confirms the paucity of Basidiomycota and basal fungi, with almost 90% attributed to Ascomycota. Reasons for the low number of Basidiomycota and basal fungi, including the Chytridiomycota, Mucoromycota, and Mortierellomycota, are advanced, including isolation procedure and media, incubation period and the slow growth of basidiomycetes, the identification of non-sporulating isolates, endophyte competition, and fungus–host interactions. We compare the detection of endophytes through culture-dependent methods and culture-independent methods, the role of fungi on senescence of the host plant, and next-generation studies.
Keywords: Chytridiomycota; Endophyte; Plant Pathogens and Fungal Diseases